Pharmacotherapy versus psychological interventions in recurrent abdominal pain: in light of new evidence - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Chronic or recurrent abdominal pain is a relevant problem, which affects more than 15% of children, adolescents and young people. Organic reason for this pain can’t be found in most cases. Recently published studies have questioned the traditional treatment schema with prescribing antispasmodics, antidepressants and other traditional drugs and shifted focus towards psychological interventions.